2022
DOI: 10.1002/ncp.10885
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of a weight‐centric approach to healthcare: A case for a paradigm shift in how clinicians address body weight

Abstract: Current healthcare is weight-centric, equating weight and health. This approach to healthcare has negative consequences on patient well-being. The aim of this article is to make a case for a paradigm shift in how clinicians view and address body weight. In this review, we (1) address common flawed assumptions in the weight-centric approach to healthcare, (2) review the weight science literature and provide evidence for the negative consequences of promoting dieting and weight loss, and (3) provide practice rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 125 publications
0
13
0
Order By: Relevance
“…In the literature, weight-inclusive programmes that focus on the social experience of living with obesity and psychological aspects of eating have been shown to provide physical and psychological benefit to patients. 39 , 40 , 41 …”
Section: Discussionmentioning
confidence: 99%
“…In the literature, weight-inclusive programmes that focus on the social experience of living with obesity and psychological aspects of eating have been shown to provide physical and psychological benefit to patients. 39 , 40 , 41 …”
Section: Discussionmentioning
confidence: 99%
“…8,9,27 Increasing evidence also suggest that weight-centric approaches are not sustainable for most people and may even be harmful, for instance by contributing to weight stigma. 28 Weight stigma often results in emotional distress (body dissatisfaction, low self-esteem and well-being, depression, etc.) and psychological stress, all of which are risk factors for ASCVD.…”
Section: Discussionmentioning
confidence: 99%
“…Weight stigma is associated with a host of adverse physical and psychological outcomes, yet remains overshadowed by the volume of literature equating weight and health ( 3 ). In a 2018 systematic review, researchers found that after controlling for weight status, weight stigma predicted elevation in biomarkers associated with hypothalamic–pituitary–adrenal axis reactivity, systemic inflammation, and type 2 diabetes mellitus ( 9 ).…”
Section: Weight Stigma Definition and Manifestationsmentioning
confidence: 99%
“…Healthcare providers are a primary source of weight stigma ( 3 , 8 , 32 , 33 ), which can lead to spending less time with and being more critical of higher-weight patients ( 34 ), along with greater reluctance to provide routine medical care and education ( 35 ). It’s also associated with poorer patient-provider communication, loss of trust and rapport, and decreased patient engagement in care, as indicated by reduced adherence to treatment recommendations and greater avoidance of healthcare ( 7 ).…”
Section: Provider Weight Biasmentioning
confidence: 99%
See 1 more Smart Citation